Coarse and fine N1 tuning for print in younger and older Chinese children: Orthography, phonology, or semantics driven?. (October 2016) - Tong, Xiuhong; Lo, Jason Chor Ming; McBride, Catherine; Ho, Connie Suk-han; Waye, Mary Miu Yee; Chung, Kevin Kien Hoa; Wong, Simpson Wai Lap; Chow, Bonnie Wing-Yin
Abstract: Visual expertise in distinguishing words from objects and word-like stimuli is a fundamental skill that is important for children to become proficient readers. This expertise can be indexed by the N1 component of ERPs at the neural level. However, the nature of N1 tuning for print is controversial in terms of onset of the latency, lateralization and the neural mechanism of the N1. This study aimed to investigate whether two groups of Chinese children could discriminate characters/character-like stimuli from visual controls (i.e., coarse N1 tuning) and distinguish characters from character-like stimuli (i.e., fine N1 tuning). We also explored the cognitive-linguistic correlates of N1 tuning. Seventeen children in the younger group ( M =7.7 years) and 13 in the older group ( M =9.4 years) were all required to finish a character decision task with character, pseudocharacter, noncharacter, and stroke combination conditions using ERP testing. Both the pseudocharacters and noncharacters were unpronounceable, and the main difference between the two conditions was in orthographic presentation (i.e., radical position). Children were also administered measures of reading fluency, reading accuracy, RAN, phonological skill and vocabulary knowledge. ERP results showed that a significantly larger N1 was observed in the characters, pseudocharacters, and noncharacters as compared to the stroke combinations in both groups. The N1 for characters and pseudocharacters was also significantly larger than that for noncharacters in both groups. Both coarse and fine N1s were larger for younger children than for older children, and the N1 was bilateral in younger children, but left lateralized in older children. Correlational analyses showed that the coarse N1 tuning of real characters versus visual controls was moderately correlated with reading fluency and accuracy but not RAN, phonology, or vocabulary. Taken together, our study suggests that both coarse and fine N1 tuning occurs in both younger and older children, when performing character decisions. Under such task demands, orthography, rather than phonology or semantics, seems to be the driver of coarse N1 tuning for print in Chinese children. Highlights: Both coarse and fine N1 tuning and the associated factors were examined. Both coarse and fine N1 tuning for Chinese print occurs in Chinese children. Coarse N1 tuning was moderately correlated with reading fluency and accuracy. Orthography appears to be the driver of coarse N1 tuning in Chinese children.